The Montessori method, Aboriginal students and Linnaean zoology taxonomy teaching: three-staged lesson - Rioux, Joël; Ewing, Bronwyn; Cooper, Tom J. (The Australian Journal of Indigenous Education, 2019)
Abstract This research article addresses an important issue related to how teachers can support Aboriginal secondary school students' learning of science. Drawn from a larger project that investigated the study of vertebrates using Queensland Indigenous knowledges and Montessori Linnaean materials to engage Indigenous secondary school students, this article focuses on the three-staged lessons from that study. Using an Action Research approach and working with participants from one secondary high school in regional Queensland with a high Indigenous population, there were several important findings. First, the materials and the three-staged lessons generated interest in learning Eurocentric science knowledge. Second, repetition, freedom and unhurried inclusion of foreign science knowledges strengthened students' Aboriginal personal identity as well as identities as science learners. Third, privileging of local Aboriginal knowledge and animal language gave rise to meaningful and contextualised Linnaean lessons and culturally responsive practices.